Model for progression of strength, power, and speed training - Kirby, T.; Erickson, T.; McBride, J. (Strength and Conditioning Journal, 2010)
Periodization is a process to sequentially and logically manipulate training variables to optimize performance for strength-power athletes, periodization models have been presented, which indicate and increasing intensity and decreasing volume of exercise with daily variations in volume and intensity as well although this addresses the progression of strength, this may not necessarily address the progression of power and speed, with power being the product of both force and velocity. This article is a discussion of the possible progression of strength, power and speed training, and not a description of a complete periodization model.